Answer:
d =
![(1)/(2)](https://img.qammunity.org/2021/formulas/physics/middle-school/ukxexrkoplrwscaxd96qbbkphc5fo6w2ur.png)
Explanation:
The n th term of an arithmetic sequence is
= a₁ + (n - 1)d
where a₁ is the first term and d the common difference , thus
a₇ = a₁ + 6d
a₄ = a₁ + 3d
Given a₇ - 2a₄ = 1 , then
a₁ + 6d - 2(a₁ + 3d) = 1, that is
a₁ + 6d - 2a₁ - 6d = 1
- a₁ = 1 ( multiply both sides by - 1 )
a₁ = - 1
Given a₃ = 0 , then
a₁ + 2d = 0 , thus
- 1 + 2d = 0 ( add 1 to both sides )
2d = 1 ( divide both sides by 2 )
d =
![(1)/(2)](https://img.qammunity.org/2021/formulas/physics/middle-school/ukxexrkoplrwscaxd96qbbkphc5fo6w2ur.png)